The effect of Indian marsh fleabane (Pluchea indica (L.) Less) dried leaves extract against oxidative stress induced by hydrogen peroxide in Saccharomyces cerevisiae - Srimoon, Rawinipa (Asia-Pacific Journal of Science and Technology, 2018)
The objective of this research was to assess the potential antioxidative capacity of Indian marsh fleabane (Pluchea indica (L.) Less) dried leaves extract. The extract was investigated the content of major groups of antioxidants, radical scavenging capacity and the effect against oxidative stress which was induced by hydrogen peroxide in Saccharomyces cerevisiae. The results showed that the extract had high concentration of antioxidants; total phenolic compounds (84.69 1.56 mg GAE/g dry weight), total tannins (69.63 0.39 mg TAE/g dry weight) and total flavonoids (45.15 1.08 mg QUE/g dry weight). The extract showed high DPPH radical scavenging activity (IC50 = 0.04 0.00 mg/ml extract and TEAC = 81.04 0.55 mg TE/g dry weight). Cellular antioxidative stress activity of the extract was determined against the stationary phase S. cerevisiae TISTR 5240 which was induced to be stressed by hydrogen peroxide (H2O2) at IC50 concentration (1.88 mM). The results revealed that the highest survival rate of S. cerevisiae was at 100 g/ml of the extract (%survival = 60.74 1.12) or 3/4 fold with respected to that of 50 μg/ml standard quercetin (%survival = 83.11 0.89). Survival rate of S. cerevisiae at the concentrations between 5.00–25.00 g/ml were significantly lower (p<0.05) compared with the control, while that of 50.00 g/ml of the extract and the control were not significant difference (p>0.05). These concentrations might be too low to scavenge free radicals. However, survival of yeast cells slightly increased with increasing the concentration of the extract pretreated to the cells. Importantly, survival rate of S. cerevisiae was significantly decreased when they were incubated with 500 and 1,000.00 g/ml of the extract due to the toxicity of the extract to the cell. From the results, P. indica dried leaves extract had high antioxidant capacity and showed antioxidant activity against H2O2 at the cellular level or cytoprotective effects. Thus, dried leaves from P. indica may be developed to the herbal tea recommended to the consumers for potential preventing the diseases caused by oxidative stress.